2014
DOI: 10.1186/1471-2229-14-34
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mechanisms linked to differentiation and function of dimorphic chloroplasts in the single cell C4 species Bienertia sinuspersici

Abstract: BackgroundIn the model single-cell C4 plant Bienertia sinuspersici, chloroplast- and nuclear-encoded photosynthetic enzymes, characteristically confined to either bundle sheath or mesophyll cells in Kranz-type C4 leaves, all occur together within individual leaf chlorenchyma cells. Intracellular separation of dimorphic chloroplasts and key enzymes within central and peripheral compartments allow for C4 carbon fixation analogous to NAD-malic enzyme (NAD-ME) Kranz type species. Several methods were used to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 77 publications
(114 reference statements)
4
19
1
Order By: Relevance
“…The selective localization of Rubisco (consisting of the nuclear-encoded rbcS and chloroplast-encoded rbcL) for function within the C 4 -D domain is one of the most definitive biochemical features of SC-C 4 . Transient expression studies using constructs expressing a GFP fusion with the B. sinuspersici rbcS plastid transit peptide in B. sinuspersici SC-C 4 mesophyll protoplasts provided no evidence for selective import within these cells ( Rosnow et al , 2014 ). In the current study, chloroplast-encoded Rubisco rbcL was used as an indicator of changes in gene expression that occurs during the differentiation of dimorphic chloroplast along the longitudinal gradient of SC-C 4 development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selective localization of Rubisco (consisting of the nuclear-encoded rbcS and chloroplast-encoded rbcL) for function within the C 4 -D domain is one of the most definitive biochemical features of SC-C 4 . Transient expression studies using constructs expressing a GFP fusion with the B. sinuspersici rbcS plastid transit peptide in B. sinuspersici SC-C 4 mesophyll protoplasts provided no evidence for selective import within these cells ( Rosnow et al , 2014 ). In the current study, chloroplast-encoded Rubisco rbcL was used as an indicator of changes in gene expression that occurs during the differentiation of dimorphic chloroplast along the longitudinal gradient of SC-C 4 development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that the rbc L-specific mRNA binding protein RLSB has a role in post-transcriptional rbc L expression and possibly selective plastid-specific accumulation of Rubisco in several C 4 species, including SC-C 4 B. sinuspersici as well as the C 4 dicots Suaeda taxifolia and Flaveria bidentis , and the C 4 monocots Zea mays and Setaria viridis ( Bowman et al , 2013 ; Rosnow et al , 2014 ). In B. sinuspersici , RLSB is co-localized with Rubisco specifically within the central compartment chloroplasts ( Rosnow et al , 2014 ), while in Kranz-type species it co-localizes with Rubisco only in BS chloroplasts. It has been proposed that RLSB and the differential redox status of the dimorphic chloroplasts might work together to selectively control synthesis of Rubisco in the C 4 -D domain in B. sinuspersici ( Rosnow et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this laser scanning confocal image, Rubisco is observed as a gold color, while the rest of the cell is observed by differential interfering contrast (DIC) imaging. Reaction of the B. sinuspersic sections with primary and secondary antisera was performed as described for Figure 1 top panel, and [13 ]. Scale bar = 50 mM.…”
Section: Factors That Affect Rbcl and Rbcs Gene Expressionmentioning
confidence: 99%
“…In mature C 4 leaves, specificity to BSC occurs at the levels of mRNA and protein accumulation (Graphical abstract, and Figure 1). In the mature leaves of plants that utilize the less common single cell C 4 system (SC-C 4 ), Rubisco is compartmentalized within only one type of dimorphic chloroplast that is localized to a specific region of the leaf chlorenchyma cell ( Figure 2) [5,12,13 ].…”
mentioning
confidence: 99%